Incorporation of Ayelala traditional religion into Nigerian criminal justice system: An opinion survey of Igbesa community people in Ogun State, Nigeria - Matthias Olufemi Dada Ojo (University of Belgrade, 2016)
Ayelala is a popular deity in the western part of Nigeria. The deity is well known for its efficacy in punishing offenders of law and order when invoked. With 52 participants, this study investigated whether Ayelala should be incorporated into Nigeria Criminal Justice and political Systems. A total of 94% of the participants agreed in one form or the other that the deity is very efficient in punishing offenders of law and order when invoked. For its inclusion in Nigeria Criminal Justice System, 54% wanted it to be included and implemented. The study, therefore, recommended that survey should be conducted in Nigerian society on whether traditional criminal justice system like Ayelala should be included in the Modern Criminal Justice System or not. If the people so desired that it should be included, government should take steps towards the implementation of the decision of the people. Other recommendations are discussed in this paper.